Distonia focal em violonistas: uma rotina de excessos - Vieira, Rudá Barreto (2023)
This study aims to discuss focal dystonia and its relationship with instrumental practice based on a case study involving three violinists who have completed their higher education. The work is the result of a qualitative research that, based on a multiple case study, sought to achieve a deep understanding of a delimited situation and the meanings for those involved. Semi-structured interviews were conducted as the data collection instrument to comprehend the individuals' trajectories and formative contexts, analyzing them as part of a set of meanings and circumstances in which these students are immersed. For the analysis process, we rely on the writings of Joaquín Farias and Ruth Chiles, researchers who provide perspectives that go beyond instrumental practice, understanding that focal dystonia is not solely a result of technical and mechanical excesses in instrumental practice. From the achieved results, it becomes evident that the onset of focal dystonia is intrinsically linked to a complex social and cultural conjuncture that permeates curricular structures and, consequently, influences the teaching and learning process of the instrument. This conjuncture encompasses factors such as competitive pressures in the job market, deeply rooted paradigms of excellence and virtuosity, lack of body awareness, absence of discussions on occupational health and musician's well-being, among other elements. These negative influences can lead to careless practice that disregards physical and mental limits, contributing to the onset of focal dystonia. Therefore, there is a need to reconsider and reformulate this model, seeking a more inclusive, healthy, and comprehensive approach to value the holistic development of music students. In light of this, this study provides a solid foundation for future research in the field of health and music education, highlighting the importance of investigating the interactions among the body, musical practice, and sociocultural context. An in-depth understanding of focal dystonia as a multidimensional manifestation enables the formulation of more comprehensive and effective preventive and therapeutic approaches.